2021
DOI: 10.3390/ijerph18147642
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health Problems as Conditions of Ex-Prisoner Re-Entry

Abstract: The article focuses on a less-discussed issue of social marginalization of people leaving penitentiaries, which is the prevalence of multifaceted health problems experienced by people in this category. It includes poor health status, resulting from, among others, poor housing conditions, harmful or risky lifestyle, and lack of access to medical services. Data from the District Inspectorate of the Prison Service in Lodz, Poland on the health conditions of inmates was accessed. These data were supplemented by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…These ndings are supported by Pekala-Wojciechowska et al (24) who identi ed frequently reported symptoms of inmates' deteriorating health while in prison, such as profound fatigue, weakness, and lethargy. Obviously these prisoners cannot effectively participate in any reformatory or rehabilitation programmes.…”
Section: Discussionsupporting
confidence: 60%
“…These ndings are supported by Pekala-Wojciechowska et al (24) who identi ed frequently reported symptoms of inmates' deteriorating health while in prison, such as profound fatigue, weakness, and lethargy. Obviously these prisoners cannot effectively participate in any reformatory or rehabilitation programmes.…”
Section: Discussionsupporting
confidence: 60%
“…While criticism has been levelled against small-scale, qualitative work in the area of music and the arts in criminal justice (Burrowes et al, 2013), this exploratory study adds to a very limited amount of research focused on adult's participation in music programmes in the community as they leave prison. The findings shine a light on participant's experiences at a transitional point that is often very fraught (Chui and Cheng, 2013;Pe ˛kala-Wojciechowska et al, 2021;Ramakers et al, 2016). As the current research has only involved men, future research could begin to consider the potential impact on women leaving prison who often have different needs as they reenter the community.…”
Section: Concluding Discussionmentioning
confidence: 90%
“…The transition from the prison regime to resettling in the community can be fraught. Former prisoners can often find themselves isolated, without money, job opportunities or clear prospects and struggling to find a direction in life (Chui and Cheng, 2013; Pękala-Wojciechowska et al , 2021; Ramakers et al , 2016). Providing support for former prisoners “through-the-gate” is important to aid resettlement and reduce risk of reoffending.…”
Section: Research Contextmentioning
confidence: 99%
“…The literature offers explanations for these patterns. Following release, formerly incarcerated adults may face challenges in accessing and receiving oral healthcare services due to a lack of transportation, health insurance, or sufficient medication to manage health conditions [16,22,23]. In fact, transportation remains one of the main barriers to acquiring proper dental care for older adults [44].…”
Section: Discussionmentioning
confidence: 99%
“…Second, threats to safety, meals with insufficient nutritious value, and lack of quality oral hygiene products while incarcerated likely contribute to worsening oral health, and these patterns may worsen the longer a person is confined [20,21]. Third, following release, formerly incarcerated adults face challenges in accessing and receiving oral healthcare services due to a lack of transportation, health insurance, or sufficient medication to manage health conditions that have oral health ramifications [16,22,23]. Hence, comparing adults with and without former incarceration status is important for understanding oral health disparities given that reentry into society necessitates navigating the US healthcare system (e.g., obtaining insurance, locating providers, and scheduling appointments).…”
mentioning
confidence: 99%